The Transforming Growth Factor-β1 (TGF-β1) Gene Polymorphisms (TGF-β1 T869C and TGF-β1 T29C) and Susceptibility to Postmenopausal Osteoporosis: A Meta-Analysis - Sun, Jiajia (Medicine (Baltimore), 2015)
The aim of the present study was to integrate all the eligible studies and investigate whether the transforming growth factor-β1 (TGF-β1) gene polymorphisms (TGF-β1 T869C and TGF-β1 T29C) are correlated with postmenopausal osteoporosis (PMOP) risk. PMOP is a common skeletal disease and several genetic factors play an important role in the development and progression of PMOP. Significant associations between TGF-β1 gene polymorphisms (TGF-β1 T869C and TGF-β1 T29C) and PMOP risk have been reported; however, some of these results are controversial. A systematic online search was performed using PubMed, EMBASE, Web of Science, and the Cochrane Library to identify case–control studies investigating the relationship between TGF-β1 T869C and TGF-β1 T29C polymorphisms and the susceptibility of PMOP. The pooled odds ratio (OR) with 95% confidence interval (95% CI) was calculated to assess the associations, and subgroup meta-analyses were performed according to the ethnicity of the study populations. Eight studies involving 1851 cases and 2247 controls met the inclusion criteria after assessment by 2 reviewers. Overall, there were significant associations between TGF-β1 T869C and TGF-β1 T29C polymorphisms and PMOP (TGF-β1 T869C—C vs T: OR = 1.18, 95% CI = 1.02–1.36, P = 0.030; CC vs TT: OR = 1.38, 95% CI = 1.01–1.88, P = 0.042; CC vs CT/TT: OR = 1.39, 95% CI = 1.09–1.76, P = 0.008; TGF-β1 T29C—CT vs TT: OR = 1.25, 95% CI = 1.02–1.53, P = 0.032; CT/CC vs TT: OR = 1.37, 95% CI = 1.02–1.84, P = 0.035). In the subgroup analysis of ethnicity, significant association was observed between TGF-β1 T869C polymorphism and PMOP risk in Asian population (C vs T: OR = 1.18, 95% CI = 1.01–1.38, P = 0.043; CC vs TT: OR = 1.41, 95% CI = 1.01–1.97, P = 0.047; CT/CC vs TT: OR = 1.31, 95% CI = 1.03–1.66, P = 0.026; CC vs CT/TT: OR = 1.35, 95% CI = 1.03–1.75, P = 0.028); however, there was no significant association between TGF-β1 T869C polymorphism and PMOP risk in Caucasian population. With regard to TGF-β1 T29C polymorphism, significant association was also observed in Asian population (CT vs TT: OR = 1.37, 95% CI = 1.07–1.75, P = 0.013; CT/CC vs TT: OR = 1.54, 95% CI = 1.16–2.05, P = 0.003), while there was no significant association in Caucasian population. The TGF-β1 T869C and TGF-β1 T29C polymorphisms may be involved in susceptibility to PMOP, particular in Asian patients.